RELATIONSHIP BETWEEN THE DURATION OF BREASTFEEDING UNTIL THE FIRST 6 MONTHS WITH BODY COMPOSITION CHANGES ON MATERNAL POSTPARTUM - Yayi Pramesti, Ajeng Arumsari (Universitas Ubudiyah Indonesia, 2015)
Most of the mothers are very attentitve to changes in body composition, especially postpartum weight loss. One of the factors believed to facilitate the weight loss and body fat loss in postpartum mothers is breastfeeding. Factor that affect the relationship between breastfeeding with maternal postpartum body composition are food intake and physical activity. The aim of this study is to analyze the change in body composition between the mother who give exclusive breastfeeding for 6 months and the mother who donât and also attempts to analyze the effect of breastfeeding duration to the change in body composition and the factor affecting it.This study used the panel study with longitudinal approach. 32 respondents observed for 6 months. Fat mass measurement data are collected using skinfold caliper and breastfeeding status, food intake and physical actiuvity data are collected using interview. The relationship between breastfeeding with the change in body composition is analyzed using t-test analysis. T-test analysis are also used to test the effect of food intake and physical activity to breastfeeding. Regression analysis are used to analyze the effect of food intake and physical activity to body composition.According to the result of statistical analysis, there is no significance effect of breastfeeding for 6 months to the change in maternal postpartum body composition (fat mass and free fat mass) (p = 0.743; p = 0.771) and also no significance effect of food intake and physical activity to the relation between breastfeeding with the change in body composition. There is a significance effect of breastfeeding for 4 months to the change in the body composition (p = 0.046). The average fat mass change in mother who give exclusive breastfeed is higher than the one who donât.From 32 respondents in this study, only 4 mothers can successfully give exclusive breastfeed for 6 months. The average fat mass change in mother who give exclusive breastfeed is higher than the one who donât. There is no significance effect of breastfeeding for 6 months to the change in maternal postpartum body composition (fat mass and free fat mass). There is a significance effect of breastfeeding for 4 months to the change in maternal postpartum body composition.Keywords: Breastfeeding, body composition, maternal postpartum